M is for Mama's boy - Buckley, Michael; Beavers, Ethen (New York : Amulet Books, 2011)
Led by Duncan "Gluestick" Dewey, the NERDS team uses brain power and courage rather than gadgets when they face off against supervillain Simon, his band of savage squirrels, and Albert, a middle-aged computer genius who lives with his mother.
5.3.
780
Accelerated Reader AR
Keywords: Superheroes -- Juvenile fiction; Schools -- Juvenile fiction; Squirrels -- Juvenile fiction; Humorous fiction; Spy stories